Metabolic interactions between acetaminophen (paracetamol) and two flavonoids, luteolin and quercetin, through in‐vitro inhibition studies. (5th September 2017) - Cao, Lei; Kwara, Awewura; Greenblatt, David J.
Abstract: Objectives: Excessive exposure to acetaminophen (APAP, paracetamol) can cause liver injury through formation of a reactive metabolite that depletes hepatic glutathione and causes hepatocellular oxidative stress and damage. Generation of this metabolite is mediated by Cytochrome‐P450 (CYP) isoforms, mainly CYP2E1. A number of naturally occurring flavonoids can mitigate APAP‐induced hepatotoxicity in experimental animal models. Our objective was to determine the mechanism of these protective effects and to evaluate possible human applicability. Methods: Two flavonoids, luteolin and quercetin, were evaluated as potential inhibitors of eight human CYP isoforms, of six UDP‐glucuronosyltransferase (UGT) isoforms and of APAP glucuronidation and sulfation. The experimental model was based on in‐vitro metabolism by human liver microsomes, using isoform‐specific substrates. Key findings: Luteolin and quercetin inhibited human CYP isoforms to varying degrees, with greatest potency towards CYP1A2 and CYP2C8. However, 50% inhibitory concentrations (IC50 values) were generally in the micromolar range. UGT isoforms were minimally inhibited. Both luteolin and quercetin inhibited APAP sulfation but not glucuronidation. Conclusions: Inhibition of human CYP activity by luteolin and quercetin occurred with IC50 values exceeding customary in‐vivo human exposure with tolerable supplemental doses of these compounds. The findings indicate that luteolin and quercetin are not likely to be of clinical value for preventing or treating APAP‐induced hepatotoxicity.